Shifting from Rote to Reasoning: The Impact of the Connected Mathematics Project Model on Elementary Students' Mathematical Skills - Dwi Harli; Yulia Astuti; Anastasya (Horizon of Primary Education, 2025)
This study aims to examine the effectiveness of implementing the Connected Mathematics Project (CMP) learning model on improving the mathematical reasoning abilities of elementary school students. The background of this study addresses the problem of students' low ability in reasoning geometric concepts, where students are often trapped in rote memorization of formulas without conceptual understanding. The researcher applied a quasi-experimental method with a Nonequivalent Control Group Design during the research process. The research subjects included all fifth-grade students of SDN 2 Tinigi, divided into two parallel classes (Experimental and Control). The test instrument collected data on reasoning abilities through valid and reliable essay questions based on four indicators: proposing conjectures, mathematical manipulation, providing reasons, and drawing conclusions. The results showed a significant increase in the experimental class with an N-Gain score of 0.88 (High Category), while the control class obtained an N-Gain score of 0.52 (Medium Category). The t-test proved that there was a significant difference between the two groups with a significance value of 0.000 < 0.05. It is concluded that the contextual problem-based CMP model is effective in improving students' mathematical reasoning abilities, especially in the aspects of proposing conjectures and mathematical manipulation.